THE APPLICATION OF LANGUAGE LEARNING STRATEGIES AND THEIR RELATIONSHIP WITH ENGLISH ACHIEVEMENT OF THE STUDENTS AT SMKN 1 SINGOSARI MALANG - WIJIANA, PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Language Learning Strategies, English Achievement, the StrategyInventory of Language Learning (SILL) Questionnaire, Heavy EquipmentDepartment. In learning English, learners often face many difficulties such as pronunciation, vocabulary, etc. So, they need learning strategies to solve them in order to improve their English skills. In Indonesian educational system, English is one of the requirements for graduation in high schools. The writer used Oxford’s (1990) theory in analyzing language learning strategies. Therefore, this study is aimed to investigate the application of language learning strategies and the relationship between language learning strategies and English achievement of 11th grade students of SMKN 1 Singosari Malang.This study used quantitative approach since the data were the scores of SILL questionnaire filled by thirty students on 11th grade at Heavy Equipment Department of  SMKN 1 Singosari Malang and their previous semester English score.This study reveals that the use of overall language learning strategies falls into medium level with the mean score of 2.60. Compensation strategies are the most frequently used with the mean score of 2.97. The following strategies used by the students are affective, metacognitive, cognitive, social and memory strategies. In addition, there is no significant relationship between the six categories of language learning strategies and their English achievement. It may be caused by their aim in learning English in which they focus more on getting a good grade rather than improving their skills.It is suggested that the teachers should introduce the appropriate language learning strategies to the students. Next, the students should be aware of using language learning strategies to enhance their achievement. For the next researchers, they can use other English achievement, additional factors influencing the choice of language learning strategies as variables, and employ more samples for future studies.